Backward capacity-filtering for electronics Fabs. Issue 11 (17th August 2016) - Seo, Jeong C.; Chung, Yong H.; Kim, Byung H.; Park, Sang C.
Abstract: In electronics Fabs such as semiconductor Fabs and liquid crystal display (LCD) Fabs, which are capital-intensive, finite-capacity planning is critical to achieving full-capacity production and on-time production. However, existing finite-capacity planning methods do not adequately reflect the actual capacity profiles of an electronics Fab. In this paper, we propose a new Fab-level capacity-filtering procedure to generate finite-capacity plan: a backward capacity-filtering procedure for generating finite-capacity release plan. When developing the Fab-level filtering procedures, we use stage-level capacity-filtering algorithms as a key building block. In this study, we enhance the previous capacity-filtering algorithms proposed by one of the authors in order to facilitate the practical requirements of electronics Fabs. We apply the proposed capacity-filtering method to a modern LCD–TFT Fab in Korea. Performance analyses demonstrate that the proposed method is superior to existing methods.